Kritik atas Penelitian NÄá¹£ir al-DÄ«n al-AlbÄnÄ« terhadap á¸¤adÄ«th yang Dinilai á¸Œaâ€˜Ä«f dalam al-JÄmiâ€˜ al-á¹¢aá¸¥Ä«á¸¥ Karya Muslim b. á¸¤ajjÄj al-NaysÄbÅ«rÄ« - Fahmi Ali Syaifuddin Rizal (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2017)
This article tries to re-read the results of research conducted by Muá¸¥ammad NÄá¹£ir al-DÄ«n al-AlbÄnÄ« against the á¸¥adÄ«ths in al-JÄmiâ€˜ al-á¹¢aá¸¥Ä«á¸¥ by Muslim b. al-á¸¤ajÄj al-NaysÄbÅ«rÄ«. He has considered weak (á¸aâ€˜Ä«f) against the twenty hadith contained in the al-JÄmiâ€˜ al-á¹¢aá¸¥Ä«á¸¥ either due to problems related to the integrity and credibility of the narrator in the course of his treasures (sanad) as well as concerning the authenticity problem of hadith texts (matn). The results of the study show that his research contains many errors due to the lack of careful understanding of the pronunciations used by the á¸¥adÄ«th critics when conducting a review of the abovementioned narrative. In addition, al-AlbÄnÄ« also lacked the extra attention in analyzing the status of the narrators assessed jará¸¥ and taâ€˜dÄ«l, so erroneously in concluding the status of narrator. It seems, he does not understand the difference of pronunciation of the á¸¥adÄ«th, ignores the shará¸¥ of the á¸¥adÄ«th, and ignores the other hadiths as a comparison in conducting research.